ANALISIS PENETAPAN NILAI JUAL OBJEK PAJAK (NJOP) ATAS PENERIMAAN PAJAK BUMI DAN BANGUNAN - Ratna Sari (Jurnal Bisnis dan Kewirausahaan, 2023)
Property Tax is one of the taxes managed by the local government, because most of the revenue is regional revenue, among others, it is also used for the provision of facilities enjoyed by the central government and local governments. The tax base of land and buildings is taxable value. The purpose of this study is to analyze the determination of taxable value of land and building tax in Sidrap Regency. The object of this study is three Sidenreng Rappang Districts in Baranti District, Kulo District, and Panca Rijang District. The data collection technique in this study is by documentation method. This study used a comparative descriptive method. Based on the results of the study, researchers concluded that the three sub-districts are Baranti, Kulo and Panca Rijang sub-districts where the districts are located in Sidrap Regency, strategically located and generate economic value. So it has a high contribution to the acceptance in Sidrap District. The Department of Revenue is responsible for determining the selling value of tax objects needs to improve the assessment and management of data, especially between the selling value of the selling price of tax objects that occur in the community so that its determination is more relevant